DAMPAK KREATIVITAS DAN INOVASI PRODUK TERHADAP KINERJA UKM DI KOTA SEMARANG - Kalil Kalil; Evant Andi Aenurohman (Jurnal Penelitian Humaniora, 2020)
SME is one of the backbones of the national economy that directly faces the competition of the ASEAN Economic Community (AEC). The role of SMEs as economic activities is expected not only to be able to meet market needs in local communities but also reduce unemployment by providing employment. The purpose of this study was to determine the effect of creativity and product innovation on business performance. This research is field research for businesspeople in the city of Semarang. The sample was selected using a purposive sampling approach, a business actor (owner or manager) who is willing to be a respondent as many as 100 respondents. The results of this study indicate that creativity and product innovation simultaneously have a positive and significant effect on the business performance of SMEs in the city of Semarang. The implications of this research can be used by SMEs to optimize creativity and improve product innovation capabilities so that it has an impact on improving performance.